Teacher Modeling Using Complex Informational Texts - Fisher, Douglas; Frey, Nancy (The Reading teacher, 2015)
Modeling in complex texts requires that teachers analyze the text for factors of qualitative complexity and then design lessons that introduce students to that complexity. In addition, teachers can model the disciplinary nature of content area texts as well as word solving and comprehension strategies. Included is a planning guide for think aloud.